Effects of clothing perception on psychological factors and tactical intentions in fencing - Aldous-Granby, J.; McCormick, A. (International Journal of Sport and Exercise Psychology, 2020)
Research shows body language can affect opponent perception, but presents inconsistencies for clothing. The consequences of clothing perception have received little attention. This study examined if clothing can affect perception in a sporting context and examined the effects of this change. Fencers (N = 63) completed a questionnaire displaying two conditions of a fencing opponent: an international condition and a club condition. Participants` judgements of the opponent, self-efficacy, outcome expectations, locus of control, and tactical intentions were measured. Results showed participants perceived the international opponent to be of a higher level (p < .001) and ability (97.4%, p < .001), and they judged them more favourably (67.8%, p < .001). Self-efficacy (-16% ±19, p < .01) and outcome expectations (-26.7%, p < .001) decreased while locus of control became more external (p < .001) against the international opponent. Participants intended to be less attacking and less assertive during the first hit and throughout the match against the international opponent (p < .025). These results show that clothing can affect opponent perception within sport, impacting key psychological performance factors and tactical intentions. This study highlights the need for further investigation into person perception in sport, especially the mechanisms causing less attacking and assertive behaviour against perceived high-level opponents. Keywords: locus of control, outcome expectations, self-efficacy, tactics